2009
DOI: 10.1016/j.neuroscience.2009.04.057
|View full text |Cite
|
Sign up to set email alerts
|

Chronic stress effects on dendritic morphology in medial prefrontal cortex: sex differences and estrogen dependence

Abstract: A growing body of work has documented sex differences in many behavioral, neurochemical, and morphological responses to stress. Chronic stress alters morphology of dendrites in medial prefrontal cortex in male rats. However, potential sex differences in stress-induced morphological changes in medial prefrontal cortex have not been examined. Thus, in Experiment 1 we assessed dendritic morphology in medial prefrontal cortex in male and female rats after chronic stress. Male and female rats underwent either three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
180
3
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(207 citation statements)
references
References 56 publications
20
180
3
4
Order By: Relevance
“…Our result extends this finding to include both genders and cortisol levels under physiological conditions as compared with levels after pharmacologic suppression. We expected a weaker association between cortisol levels and brain morphology in women than men, based on experimental data (18,30), but this was not supported by our results. Importantly, all women in our sample were older than 55 years and thus were probably postmenopausal.…”
Section: :2 123 Clinical Studycontrasting
confidence: 86%
See 1 more Smart Citation
“…Our result extends this finding to include both genders and cortisol levels under physiological conditions as compared with levels after pharmacologic suppression. We expected a weaker association between cortisol levels and brain morphology in women than men, based on experimental data (18,30), but this was not supported by our results. Importantly, all women in our sample were older than 55 years and thus were probably postmenopausal.…”
Section: :2 123 Clinical Studycontrasting
confidence: 86%
“…High salivary cortisol levels have also been related to a thinner cortex in several PFC regions in healthy men (15), but this has not been tested in women. Importantly, experimental research suggests gender-specific differences in the effects of glucocorticoids on PFC and HC neurons (17,18). Furthermore, a putative association between cortisol levels and HC volume is confounded by small samples (9), coexisting depression (13) or cardiovascular disease (14).…”
Section: Introductionmentioning
confidence: 99%
“…There are sex differences in response to chronic stress in mPFC neurons, in which female rats with intact ovaries or estrogen treatment after ovariectomy showed an expansion of dendrites, whereas males show a chronic stress-induced retraction (Garrett and Wellman, 2009). Refining this in terms of where mPFC neurons project, Shansky showed that female rats fail to show the mPFC dendritic remodeling seen in males after CRS in those neurons that do not project to amygdala.…”
Section: Females Respond Differently To Chronic Stressmentioning
confidence: 99%
“…To our knowledge, no study has investigated the effects of stress on infralimbic neuronal architecture in female rats. Nevertheless, a recent study showed higher morphological complexity of pyramidal neurons in the anterior cingulate and prelimbic cortices when adult female rats are exposed to chronic stress (Garrett & Wellman, 2009). Yet, we should bear in mind that the current knowledge of the structural changes in the prefrontal cortex induced by exposure to stress came from studies in adult animals.…”
Section: Sex-related Differences In Brain Metabolic Activation Duringmentioning
confidence: 99%
“…So far, the majority of studies imaging metabolic activation during extinction in rodents have focused on males (mainly adults) (Bruchey, Shumake, & Gonzalez-Lima, 2007;Hefner et al, 2008;Herry & Mons, 2004;Muigg et al, 2008). Yet it is becoming increasingly clear that females differ from males in their morphological and behavioral responses to stress and brain response to various stimuli (Garrett & Wellman, 2009;Maeng, Waddell, & Shors, 2010).…”
Section: Introductionmentioning
confidence: 99%